Calcaneotibial screws for immobilisation of the tarsocrural joint of dogs in extension: effect of the angle of screw placement on the force to failure in a canine cadaveric model. Issue 5 (27th July 2021) - Devereux, S; Jack, M; Worth, A; Bridges, J
ABSTRACT: Aims: To compare the force to failure under axial loading of a calcaneotibial screw placed approximately perpendicular to the tibia with that of a screw placed perpendicular to the calcaneus, when used to immobilise the tarsus in an ex vivo canine model. Methods: Twelve pairs of cadaveric hindlimbs from large breed dogs, without orthopaedic or soft tissue disease, were prepared by transecting the limb at the level of the stifle and stripping the limbs of all musculature from the stifle to mid-metatarsus, including removal of the common calcaneal tendon from all limbs. The limbs in each pair were randomly assigned to receive a calcaneotibial screw placed perpendicular to the long axis of either the calcaneus (C group) or the tibia (T group) with the tarsus in full extension. The distal limb was potted in resin and the proximal tibia was pinned to allow biomechanical testing in compressive loading. Testing was performed to apply an axial load using a material testing machine in a proximodistal direction through the tibia, advancing at a rate of 10 mm/second. The force to failure was recorded in kN and compared between groups. Results: The median force to failure of the C group was 0.86 (min 0.50; max 1.64) kN which was higher than the T group which had a median force to failure of 0.74 (min 0.26, max1.05) kN (p = 0.004). All modes of failure were by screw pull-out. Conclusions: A calcaneotibial screw placed at an angle approximately perpendicular to the long axis of the calcaneus, has a higher force to failure under axial loading than a calcaneotibial screw that is placed at an angle approximately perpendicular to the tibia, in a canine cadaveric model. Clinical relevance: A temporary calcaneotibial screw is a common method of immobilising the tarsus in extension to protect primary repair of a common calcaneal tendon injury. Placing a calcaneotibial screw perpendicular to the calcaneus may be a more reliable option for immobilisation of the tarsus to protect a common calcaneal tendon repair compared to screws placed perpendicular to the tibia. However extrapolation of these results into a clinical setting requires caution.